2017
DOI: 10.1089/mdr.2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of a Multidrug-Resistant VIM-1- and CMY-99-ProducingProteus mirabilisClone in Bulgaria

Abstract: The aim of this study was to analyze the beta-lactamases and the molecular epidemiology of 19 clinically significant isolates of Proteus mirabilis with decreased susceptibility to imipenem, which have been collected from seven hospitals, located in different Bulgarian towns (Sofia, Varna, and Pleven). The isolates were obtained from blood, urine, tracheal and wound specimens. One additional isolate from hospital environment was included. Susceptibility testing, conjugation experiments, and plasmid replicon typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Such a frequent association between carbapenemase-producing and RMTase-producing Enterobacterales was already reported in different parts of the world [5][6][7][8][9][10][11][12][13]21,[27][28][29][30][31][32][33][34][35][36][37]. The origin of those isolates being identified in Switzerland could be autochthonous theoretically; nevertheless, clinical information (only partially obtained and therefore not presented in that study) showed that many of them corresponded to imported cases, and particularly from Eastern European countries, from Italy, and from the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 72%
“…Such a frequent association between carbapenemase-producing and RMTase-producing Enterobacterales was already reported in different parts of the world [5][6][7][8][9][10][11][12][13]21,[27][28][29][30][31][32][33][34][35][36][37]. The origin of those isolates being identified in Switzerland could be autochthonous theoretically; nevertheless, clinical information (only partially obtained and therefore not presented in that study) showed that many of them corresponded to imported cases, and particularly from Eastern European countries, from Italy, and from the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 72%
“…The bla VIM−1 gene is located on class 1 integrons, inserted into the chromosome with genes aacA7, dhfr, and aadA (Vourli et al, 2006) or in conjugative plasmids carrying also bla VEB−1 , bla OXA−10 , bla TEM−1 genes (Papagiannitsis et al, 2012). In addition, an outbreak of 13 P. mirabilis isolates producing VIM-1 and CMY-99 was recently reported in Bulgaria (Markovska et al, 2017). In this clone, the bla VIM−1 gene was located into a class 1 integron that also contained the aminoglycoside (aac(6 )-Ib, ant(3 )-Ia) and trimethoprim (dhfrA1) resistance determinants (Markovska et al, 2017) Two other isolates of P. mirabilis co-producing VIM-1 and CMY-16 have also been described in the Netherlands (van Dijk et al, 2014).…”
Section: Vim-1mentioning
confidence: 99%
“…In addition, an outbreak of 13 P. mirabilis isolates producing VIM-1 and CMY-99 was recently reported in Bulgaria (Markovska et al, 2017). In this clone, the bla VIM−1 gene was located into a class 1 integron that also contained the aminoglycoside (aac(6 )-Ib, ant(3 )-Ia) and trimethoprim (dhfrA1) resistance determinants (Markovska et al, 2017) Two other isolates of P. mirabilis co-producing VIM-1 and CMY-16 have also been described in the Netherlands (van Dijk et al, 2014).…”
Section: Vim-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most prevalent carbapenemases in Enterobacterales were sporadically described in P. mirabilis isolates including KPC-2, VIM-1, IMP-like, NDM-1 and OXA-48 [7][8][9] .…”
mentioning
confidence: 99%